Performance Evaluation of Self‐Degradable Gel Temporary Plugging Agents for Pressurized Workover - Deji Liu; Chao Chen; Xiaohui Li; Ying Wang; Li Cheng; Shoumin Sun; Jiayi Tan (Energy Science & Engineering)
ABSTRACT Band pressure operation has become the main way of oil and gas well workover in the world, to solve the gel breaking problem in the gel plugging pressure technology, acrylamide and ester‐based cross‐linking agent UCL‐1 were used to synthesize a self‐degradable gel that can be used at 40°C–60°C by the one‐pot method. The cross‐linking reaction principle of the gel was analyzed by infrared spectroscopy; in addition, the degradation performance of the gel and the effects of acrylamide, UCL‐1, initiator and metal ions on the degradation performance of the gel as well as the influence law were investigated; finally, sand‐filled tubing and casing were used to simulate the stratigraphy and the wellbore, respectively, thus evaluating the sealing performance of the gel. The results showed that the cross‐linking reaction of the gel was a double‐bond copolymerization reaction; the viscosity of the gel after complete degradation in the range of 40°C–60°C was 51–450 mPa‐s, and the degradation time was 115–220 h, and the degradation time of the gel could be adjusted by changing the formulation components and the mineralization degree; moreover, the pressure‐bearing capacity of the gel in the formation at 40°C–60°C was 8.5–14.9 MPa, and the pressure‐bearing capacity of gel in wellbore is 52–73 kPa, and the blocking time is 3–6 d, which meets the construction time requirement of pressurized operation. This study extends the breaking method of gel plugging pressure technology and further promotes the development and application of pressure work technology.